Prevalence and Trends of Drinking Water Disinfection Byproducts-Related Cancers in Addis Ababa, Ethiopia - Nebiyou Tafesse; Massimiliano Porcelli; Sirak Robele Gari; Argaw Ambelu (SAGE Publishing, 2022)
Background: Disinfection byproducts (DBPs) from chlorinated drinking water have been linked to an increased risk of cancer in the bladder, stomach, colon, and rectum. No studies showed the independent trends and prevalence of these cancers in Ethiopia. Therefore, this study aimed to determine the prevalence and trends of disinfection byproducts-related cancers in Addis Ababa, Ethiopia. Methods: Data were collected from the Addis Ababa Cancer Registry. Spatial data sets were produced and classified into households receiving chlorinated surface water and less chlorinated groundwater. The Cochran-Armitage trend test was used to evaluate whether there was a disinfection byproducts-related cancers (DBRCs) trend among communities receiving chlorinated water. Negative binomial regression was used to analyze the incidence rate. Results: A total of 11, 438 cancer cases were registered between 2012 and 2016, and DBRCs accounted for approximately 17%. The majority of the total cancer cases were female; 7,706 (67%). The prevalence of DBRCs was found to be higher in communities supplied with chlorinated water. From 2012 to 2016, the trend of colon cancer increased (β = 10.3, P value = .034); however, esophageal cancer decreased (β = −6.5, P value = .018). Approximately 56% of colorectal cancer patients and 53% of stomach cancer patients are known to be using chlorinated surface water for drinking regularly. In addition, approximately 57.1% and 54% of kidney and bladder cancer patients, respectively, used chlorinated surface water. Conclusion: The prevalence of DBRCs in this study was found to be high. The colon cancer trend increased substantially from 2012 to 2016. The prevalence of DBRCs was higher in communities supplied with chlorinated surface water. Similarly, the prevalence of DBRCs was higher among males than females. Further study is required to validate the association between DBRCs and water chlorination.